Comparative analysis of peri-nidal cerebral blood flow and metabolism using a novel quantitative 15O-PET method in patients with arteriovenous malformations - Maruyama, Daisuke; Iida, Hidehiro; Koshino, Kazuhiro; Nakagawara, Jyoji; Morita, Yoshiaki; Hashimura, Naoki; Mori, Hisae; Satow, Tetsu; Takahashi, Jun C.; Fukuda, Tetsuya; Iihara, Koji; Kataoka, Hiroharu (SAGE, 2025)
To effectively treat cerebral arteriovenous malformations (AVMs), peri-nidal flow regulation and metabolic status must be understood. In this study, we used 15O-oxygen positron emission tomography (PET) post-processing analysis to investigate vascular radioactivity in the nidal region of AVMs. Single-dynamic PET imaging was performed on seven unruptured AVM patients during the sequential inhalation of 15O2 and C15O2. A previously validated dual-tracer basis function method (DBFM) was employed to calculate parametric images. The results of our study were as follows. First, in remote and contralateral AVM regions, DBFM and a previous approach of dual-tracer autoradiography (DARG) showed strong positive correlations in cerebral blood flow (CBF), cerebral oxygen metabolism rate (CMRO2), and oxygen extraction fraction. Second, peri-nidal CBF and CMRO2 correlation was lower, and overestimation occurred with DARG compared to with DBFM. Third, on comparing DBFM to quantitative 123I-iodoamphetamine single-photon emission computed tomography (SPECT), CBF correlated significantly. In contrast, the correlation between DARG and quantitative 123I-iodoamphetamine-SPECT was weaker in the peri-nidal regions. Fourth, analysis of tissue time-activity curves demonstrated good reproducibility using the novel formulation in the control, peri-nidus, and core nidal regions, indicating the adequacy of this approach. Overall, the DBFM approach holds promise for assessing haemodynamic alterations in patients with AVMs.